2003
DOI: 10.1007/s00493-003-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Complexes of Stable Kneser Graphs

Abstract: It is shown that the neighborhood complexes of a family of vertex critical subgraphs of Kneser graphs -the stable Kneser graphs introduced by L. Schrijver -are spheres up to homotopy. Furthermore, it is shown that the neighborhood complexes of a subclass of the stable Kneser graphs contain the boundaries of associahedra (simplicial complexes encoding triangulations of a polygon) as a strong deformation retract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…Note that this kind of edges has already been considered and named quasistable in a paper by Björner and de Longueville [3].…”
Section: Resultsmentioning
confidence: 92%
“…Note that this kind of edges has already been considered and named quasistable in a paper by Björner and de Longueville [3].…”
Section: Resultsmentioning
confidence: 92%
“…The box complexes of Schrijver graphs are tidy as well (spheres up to homotopy [3]). This means that one can prove Kneser's conjecture using Sarkaria's bound (or any higher suspension of the box complex).…”
Section: Remark 32mentioning
confidence: 99%
“…We have not seen this connection made explicit in the literature, even though Ziegler [24] combined ideas from both proofs and work by Matoušek [17] in a combinatorial proof of χ (SG n,k ) = k + 2 and even though the vertex criticality of stable Kneser graphs had suggested that the neighbourhood complex N (SG n,k ) is homotopy equivalent to a k-sphere, which was proved by Björner and de Longueville [5].…”
Section: Detailed Overview and Resultsmentioning
confidence: 99%
“…The construction of Section 3 leads to a more conceptual proof of the homotopy equivalence N (SG n,k ) S k of [5] and, using the result of Section 4, also of the following D 2m -equivariant version.…”
Section: Homotopymentioning
confidence: 99%